KONTEKSTUALISASI PEMIKIRAN MAQÂSID AL-SHARÎ’AH JASSER AUDA TERHADAP PENDIDIKAN ANAK USIA DINI - Dahlia (Wahana Islamika: Jurnal Studi Keislaman, 2019)
Islamic law must be oriented to the maqâsid al-sharî'ah, namely the benefit of mankind. However, Islamic law has always seemed rigid, so when faced with diverse realities, it seemed unable to provide a solution. In fact, a law was made with the aim of providing comfort, security, and welfare for human life. This study aims to explain the approach of Jasser Auda's proposed system and its contextualization of early childhood education. The type of research used is library research. The data source uses secondary sources, namely Jasser Auda's work entitled Maqasid al-Shari'ah as Philosophy of Islamic Law: A Systems Approach and relevant journals. Data analysis uses inductive analysis. The results of this study indicate that, through a system approach, Jasser Auda offers a concept for the development of Islamic law in the current era. The system approach proposed by Jasser Auda includes six interconnected features, namely: cognitive nature, wholeness, openness, interrelated hierarchy, multi-dimensionality, and purposefulness. The system approach can be contextualized in the world of PAUD, for example in the preparation of a strategic plan (RENSTRA). The purpose of early childhood education (PAUD), is to grow and develop physical and spiritual learners in order to have readiness in entering further education (purposefulness). To realize this goal, PAUD agencies must have a RENSTRA. The preparation of RENSTRA is based on the results of human cognition (cognitive nature) which prioritizes holistic thinking (wholeness), as well as involving various education experts (multi-dimensionality). So that the RENSTRA that has been prepared can be applied properly, it takes the pattern of relations of foundations, principals, teachers, and all the components that manage these agencies can synergize (interrelated hierarchy) and openness.